The Impact of Artificial Intelligence Utilization on The Media Industry in Indonesia: A Case Study On Suara.Com and Rri - Shafa Salsabila Gusna; Bonaventura Satya Bharata (ULTIMA Comm, 2024)
This study examines the impact of AI utilization on human resources in the media industry in Indonesia with a case study of Suara.com and RRI. This study is relevant in the context of media management. However, research shows that there are concerns about job losses for workers in the media industry. This study identifies and analyzes aspects of AI technology acceptance by media management in Indonesia and the consequences of AI adoption on HR. The results of the study show that the acceptance of AI technology is an urgent need for Suara.com and RRI media management to respond to changing digital trends. Suara.com is aware of the changing role of traditional journalists along with the increasing need for new skills to operate AI. Meanwhile, RRI manages HR steadily by focusing on training to adapt to new technologies. Journalists will be the verifiers of all information circulating and will act as content providers for AI-based platforms. Without the presence of journalists, AI platforms will not have access to the latest, credible, and relevant content. The results of this study are expected to be a reference for the development of more inclusive and sustainable media management policies.